2009
DOI: 10.1080/07399330902928824
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Husbands' Migration on Mental Health and Gender Role Ideology of Rural Mexican Women

Abstract: Our purpose for this study was to investigate the roles of migration in rural Mexican migrant-sending communities. Specifically, we examined the effects of changing gender role ideology on the mental health of wives whose spouses migrated to the United States. The sending group scored significantly higher in egalitarian gender role ideology but lower in general mental health than the nonsending group. We found through mediation analysis that the difference in gender role ideology mediated the difference in men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 26 publications
3
14
0
Order By: Relevance
“…Some studies also showed that lone mothers are more likely to have long term illnesses and die more often than married mothers [13, 14]. In some cases, migration of husbands decreased the mental health of their wives [15]. Divorced, widowed and separated women are more likely to have problems in paying their medical bills than either single or married women [3].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies also showed that lone mothers are more likely to have long term illnesses and die more often than married mothers [13, 14]. In some cases, migration of husbands decreased the mental health of their wives [15]. Divorced, widowed and separated women are more likely to have problems in paying their medical bills than either single or married women [3].…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of work shows that migration-induced separation between family members has adverse effects on the psychological wellbeing of those who remain behind (Wilkerson et al, 2009). Migration deprives family members of the instrumental and social support of key family members (Kanaiaupuni, 2000).…”
Section: Stressmentioning
confidence: 99%
“…The belief that people change their gender roles and ideologies both between and within generations is gaining acceptance (Wentworth & Chell, 2005), leading researchers to believe that these roles are not created through biology but mainly develop through environmental influences (Cunningham, 2001). Women are expected to expand their roles when they participate in education and the workplace, which might lead them to shift away from traditional gender roles (Wilkerson, Yamawaki, & Downs, 2009). Further, women's exposure to the labor force is expected to foster more egalitarian gender attitudes (Smith-Lovin & Tickamayer, 1978).…”
Section: Gender Ideologymentioning
confidence: 99%